Mesoporous copper-based catalyst and preparation method thereof

Through the synthesis of mesoporous copper-based catalysts, soft templates and wet impregnation methods are used to form a mesoporous silica support with high specific surface area. Combining copper salts and lanthanum oxide, the efficiency of carbon dioxide hydrogenation to produce methanol under non-thermal plasma driven is solved. The problem of low efficiency catalysis and high selectivity methanol production are achieved, and the stability and economicality of the catalyst are ensured.

CN119215963APending Publication Date: 2024-12-31ZHEJIANG TIHE INSTR
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411562820.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

In the prior art, the catalyst used for non-thermal plasma-driven carbon dioxide hydrogenation to produce methanol is inefficient and it is difficult to effectively catalyze the reaction under mild conditions.

Method used

The mesoporous copper-based catalyst was used to synthesize through a two-step method of combining soft template and wet impregnation. The pH was adjusted using cetyl trimethylammonium chloride as a template agent and ammonia water to form a high specific surface area and ordered pores. Mesoporous silica support, combining copper salt and lanthanum oxide, improves the activity and selectivity of the catalyst.

Benefits of technology

It realizes efficient catalytic conversion of carbon dioxide into methanol under mild conditions, improves the selectivity and yield of methanol, and the catalyst has good high temperature stability and low preparation cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119215963A_ABST
    Figure CN119215963A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of catalysis, and particularly relates to a mesoporous copper-based catalyst and a preparation method thereof. The method comprises the following steps: 1) uniformly mixing a template agent solution, alkali liquor and a dispersing agent, dropwise adding an organosilicon compound, hydrolyzing to obtain a milk white mixed solution, carrying out suction filtration on the milk white mixed solution, cleaning a filter cake, drying, and calcining to obtain a carrier; and 2) uniformly mixing a copper salt, a lanthanum salt and a solvent, adding the carrier for dipping, and drying, calcining, grinding, screening and performing hydrogen reduction on the product to obtain the mesoporous copper-based catalyst. The catalyst provided by the invention is simple and effective in synthesis method, low in preparation cost, high in success rate of catalyst preparation, large in catalyst yield, high in specific surface area and highly ordered in mesoporous channel, can improve the conversion rate of carbon dioxide, can generate methanol with high selectivity, and improves the production efficiency of methanol.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of catalysis, and in particular relates to a mesoporous copper-based catalyst for non-thermal plasma driven carbon dioxide hydrogenation to methanol and a preparation method thereof. Background Art

[0002] Carbon dioxide is a major greenhouse gas. In order to reduce the environmental impact of excessive carbon dioxide emissions, methods for capturing, storing, and converting carbon dioxide are particularly important. Converting carbon dioxide into high-value-added chemical raw materials or products through catalysis is an important way to achieve effective utilization of carbon dioxide. Among them, carbon dioxide is generally directly hydrogenated and catalytically converted into methanol, which can then be further synthesized into high-value-added chemicals such as olefins, gasoline, biodiesel, and fuel additives. This approach can meet huge industrial needs and has good prospects. The hydrogenation of carbon dioxide to methanol is an exothermic reaction. In order to promote the dissociation of carbon dioxide molecules and the selective generation of methanol, it is often prepared under low temperature and high pressure conditions. In order to be able to efficiently convert carbon dioxide and synthesize methanol under mild conditions, and to promote the development of conversion technology, it is necessary to find a catalytic method that is suitable for mild conditions and can proceed spontaneously.

[0003] Non-thermal plasma is a highly efficient catalytic method that uses an external high-voltage electric field to promote the activation and dissociation of carbon dioxide molecules in a non-equilibrium thermodynamic state (usually at room temperature and pressure), generating a variety of active species (such as excited molecules, free radicals and free electrons, etc.), and achieving atomic / molecular scale reaction process intensification. The synergistic effect of non-thermal plasma and catalysts can drive chemical reactions that are difficult to spontaneously carry out under mild conditions or are thermodynamically unfavorable at room temperature and pressure, such as carbon dioxide hydrogenation to produce hydrocarbon fuels (such as methane, methanol, etc.), water vapor shift hydrogen production, and synthetic ammonia.

[0004] At present, there is a lack of research on efficient catalysts for non-thermal plasma driven carbon dioxide hydrogenation. Among them, copper-based catalysts are the most widely used. Cu and ZnO composite catalysts are believed to be able to effectively promote catalytic reactions. For catalytic carriers, whether in traditional thermal catalysis or plasma-assisted catalysis, porous materials (such as molecular sieves, mesoporous silica, porous alumina, etc.) are widely used in the catalytic conversion of carbon dioxide due to their high specific surface area, specifically designed pores or surface structures. However, in the field of non-thermal plasma, there are few patents and public documents on the use of copper-based catalysts to catalyze the hydrogenation of carbon dioxide to methanol, and there has been no report on the use of mesoporous silica as a carrier in plasma-driven carbon dioxide hydrogenation to methanol. Summary of the invention

[0005] Based on the above content, in order to solve the problems of low yield and poor methanol selectivity of carbon dioxide hydrogenation to methanol, the present invention proposes a mesoporous copper-based catalyst for non-thermal plasma driven carbon dioxide hydrogenation to methanol and a preparation method thereof.

[0006] The objects of the present invention are:

[0007] 1. To provide a simple method for preparing a high-performance carbon dioxide hydrogenation catalyst;

[0008] 2. Prepare a new catalyst to efficiently catalyze the hydrogenation of carbon dioxide and improve the product yield;

[0009] 3. Improve the selectivity of the catalyst for methanol and increase the purity of the target product.

[0010] To achieve the above objectives, the present invention adopts the following technical solutions.

[0011] A method for preparing a mesoporous copper-based catalyst.

[0012] The method comprises:

[0013] 1) taking a template solution, an alkali solution and a dispersant and mixing them evenly, adding an organosilicon compound dropwise to hydrolyze to obtain a milky white mixed solution, filtering the mixed solution, washing the filter cake and drying it, and calcining the mixture to obtain a carrier;

[0014] 2) Evenly mix copper salt, lanthanum salt and solvent, add the mixture into a carrier for impregnation, dry, calcine, grind and screen the product and reduce it with hydrogen to obtain a mesoporous copper-based catalyst.

[0015] As a preference,

[0016] Step 1) the template solution is a hexadecyltrimethylammonium chloride aqueous solution with a concentration of 20-25 wt%;

[0017] Step 1) The alkali solution is saturated ammonia water, and its dosage is 0.97-6.49 mL / mL template solution;

[0018] Step 1) The dispersant is water, and its dosage is 10-15 mL / mL template solution;

[0019] In step 1), the organosilicon compound is tetraethoxysilane, and its usage is 0.92-2.77 mL / mL template solution.

[0020] As a preference,

[0021] The hydrolysis in step 1) is carried out under continuous stirring at room temperature for 4 to 5 hours;

[0022] Step 1) The calcination is carried out at 500-600° C. for 5-7 hours.

[0023] As a preference,

[0024] Step 2) the copper salt is copper nitrate and / or copper acetate and / or copper chloride and / or copper oxalate and / or copper sulfate and / or copper acetylacetonate;

[0025] Step 2) the lanthanum salt is lanthanum nitrate and / or lanthanum acetate and / or lanthanum oxalate and / or lanthanum acetylacetonate and / or lanthanum chloride and / or lanthanum sulfate;

[0026] Step 2) The copper salt and the lanthanum salt are prepared in a mass ratio of 1: (0.3-6.0).

[0027] As a preference,

[0028] Step 2) the solvent is ethanol, and the amount used is 115-155 mL / g copper salt;

[0029] Step 2) The amount of the carrier used is 5.9-7.7 g / g copper salt.

[0030] As a preference,

[0031] Step 2) The impregnation process is:

[0032] Stir at room temperature for 22 to 26 hours, then stir at 30 to 40°C to evaporate until the solution is evaporated to dryness;

[0033] Step 2) The calcination is carried out at 400-500° C. for 2-4 hours.

[0034] As a preference,

[0035] Step 2) The hydrogen reduction process is:

[0036] Hydrogen and argon are mixed in a ratio of (2-4):7 to obtain a mixed gas, and the mixed gas is introduced at a rate of 40-45 mL / min. The temperature is adjusted to 300-500° C. and maintained at a constant temperature for 1-2 hours.

[0037] A mesoporous copper-based catalyst.

[0038] In order to achieve efficient conversion of carbon dioxide and improve methanol selectivity, the present invention studies the surface area of ​​the carrier, the content of active sites, the dispersion of materials, additives, preparation conditions and other aspects. In the technical scheme of the present invention, in order to improve the purity of the catalyst, a two-step method combining soft template and wet impregnation is used to synthesize a mesoporous copper-based catalyst Cu for non-thermal plasma driven carbon dioxide hydrogenation to methanol. x La y / MCM-41. The invention firstly adopts a soft template self-assembly method to prepare an ordered mesoporous silica carrier, uses hexadecyltrimethylammonium chloride as a template, adjusts the pH value of the solution with ammonia water, and drips tetraethoxysilane drop by drop to mix.

[0039] In this process, the present invention utilizes the longer hydrophobic alkyl chain of hexadecyl trimethyl ammonium chloride, and self-assembles with the hydrophilic quaternary ammonium salt head to form micelles, and these micelles can be used as templates to induce materials to form mesoporous channels with unobstructed pore volume on a microscopic scale. The presence of hexadecyl trimethyl ammonium chloride molecules limits crystal growth, so that crystals grow along the spatial structure formed by the molecules, thereby regulating and controlling the carrier pore size and porosity. Hexadecyl trimethyl ammonium chloride molecules are adsorbed on crystal faces, suppress the growth of the crystal faces, and make other crystal faces relatively easy to grow up, which is conducive to obtaining high-porosity carriers, significantly affecting the effective specific surface area of ​​the material, which plays an important role in adsorbing carbon dioxide and catalyzing its conversion. The structure induced by hexadecyl trimethyl ammonium chloride has good thermal stability and can extend the service life of the material. Obviously, the molecular arrangement mode of the template agent can affect the morphology of the pore channel, and more importantly, increasing the template agent concentration can increase the pore volume, form a larger space, and is conducive to active species loading.

[0040] At the same time, the present invention adjusts the solution to alkalinity by ammonia, which is conducive to improving the synthesis efficiency and structural stability of mesoporous silica. By regulating the amount of ammonia to regulate the pH of the solution, the hydrolysis rate of tetraethoxysilane and the degree of polycondensation of silanol after hydrolysis can be controlled, and the surface charge of silanol (negatively charged under alkaline conditions) is changed at the same time, which is conducive to the effective component to fully form a target carrier along the spatial structure constructed by the positive cation hexadecyltrimethylammonium. After tetraethoxysilane is fully hydrolyzed and condensed, the silica particles of the spatial structure constructed along the hexadecyltrimethylammonium chloride are obtained, and then the material is calcined to obtain a mesoporous skeleton supported by silica.

[0041] Subsequently, the present invention disperses a certain amount of metal source in ethanol, adds a dry mesoporous carrier to wet impregnate the loaded active component, and reduces and prepares a copper-based lanthanum oxide composite catalyst. After the copper salt and lanthanum salt are evenly distributed on the carrier, the present invention removes the residual hexadecyltrimethylammonium chloride by high-temperature calcination, and in the process, lanthanum nitrate decomposes and forms a lanthanum oxide promoting component with uniform particle morphology and good dispersibility. On the one hand, this component improves the dispersity and contact area of ​​the copper active component through interaction with the copper active component, and on the other hand, through the characteristics of its alkaline oxide, improves the physicochemical adsorption performance of the acidic gas molecule carbon dioxide, thereby ensuring the effect of the catalyst adsorption and conversion of carbon dioxide, and improving the carbon dioxide conversion rate and methanol yield.

[0042] In copper-based lanthanum oxide composite catalysts, the active component Cu is mostly Cu 0 , carbon dioxide is Cu 0The main carbon source for surface hydrogenation reaction, and the rate of carbon dioxide hydrogenation is faster than that of carbon monoxide, and the rate of methanol production is significantly improved. The increase in the dispersion of copper species is conducive to the activation of hydrogen in Cu 0 The present invention regulates the relative amount of copper salt and carrier by studying the performance of the catalyst under different copper loadings, thereby improving the catalytic activity of the catalyst and thus improving the carbon dioxide conversion rate. The low copper loading causes the formation of smaller particles on the catalyst surface, and the methanol selectivity is low at this time. Therefore, although the number of highly dispersed active species is large, the total loading is insufficient, resulting in the inability to maintain excellent catalytic activity. As the copper loading on the carrier increases, hydrogen is 0 The reaction activity at the site is high, and the methanol selectivity increases, but the dispersion of copper species is getting lower and lower, and the area of ​​active sites exposed in the catalyst first increases and then decreases. When the copper loading is high, the methanol selectivity remains almost unchanged. It can be seen that appropriate copper loading is conducive to improving methanol selectivity and yield.

[0043] Next, the present invention also studies the effect of different relative amounts of copper salts and lanthanum salts on the performance of the catalyst. An appropriate amount of lanthanum oxide can provide reactive centers for the overflowing carbon dioxide, and part of the multivalent lanthanum oxide migrates to the surface of the catalyst, forming Cu near it. + As the active center for synthesizing methanol, CO is generally formed on lanthanum trioxide. According to the relative content of multivalent lanthanum oxide substances, the changes in the catalytic activity of the catalyst and the changes in the methanol selectivity can be compared.

[0044] Generally speaking, calcination conditions will affect the performance of the catalyst. The mesoporous silica skeleton is distributed in the catalyst of the present invention. Too high a temperature will reduce the order of the material, causing the collapse of some mesoporous channel structures, a decrease in the channel volume, and a poor ability to adsorb carbon dioxide due to channel dispersion, thereby causing a decrease in the carbon dioxide conversion rate. The catalyst sintered at a constant temperature at an appropriate calcination temperature has a short-range ordered three-dimensional structure.

[0045] The reduction temperature also has a great influence on the catalyst. Due to the presence of copper lanthanum active species, the interaction between it and the carrier is enhanced, so the required reduction temperature is relatively high. As the reduction temperature increases, the catalytic activity of the catalyst becomes higher, and the methanol selectivity and yield are higher. Too high a reduction temperature will lead to a decrease in catalyst performance.

[0046] In summary, the copper-based catalyst prepared by the present invention uses ordered mesoporous silica as a carrier, and the copper-lanthanum active component is uniformly loaded on the surface of the carrier, where copper and lanthanum oxide are active components and promoters, respectively. This ensures that the catalyst can be plasma-driven to hydrogenate carbon dioxide to methanol under mild conditions, and exhibits good catalytic effects under non-thermal plasma driving.

[0047] The beneficial effects of the present invention are as follows:

[0048] (1) The catalyst synthesis method provided by the present invention is simple and effective, has low preparation cost, high success rate for preparing the catalyst, and large catalyst yield;

[0049] (2) The catalyst prepared by the present invention has a high specific surface area and highly ordered mesoporous channels, which can improve the carbon dioxide conversion rate;

[0050] (3) The catalyst prepared by the present invention can generate methanol with high selectivity, thereby improving the production efficiency of methanol. BRIEF DESCRIPTION OF THE DRAWINGS

[0051] Figure 1 This is an elemental high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) structure diagram of the mesoporous copper-based catalyst in Example 3.

[0052] Figure 2 This is the EDS-Mapping elemental structure diagram of the mesoporous copper-based catalyst in Example 3. DETAILED DESCRIPTION

[0053] The present invention is further described in detail below in conjunction with specific embodiments and the accompanying drawings. A person of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are generally only embodiments of a part of the present invention, rather than all embodiments. Therefore, based on the embodiments of the present invention, all other embodiments obtained by a person of ordinary skill in the art without making creative work should fall within the scope of protection of the present invention.

[0054] Unless otherwise specified, the raw materials used in the examples of the present invention are all commercially available or available to those skilled in the art; unless otherwise specified, the methods used in the examples of the present invention are all methods known to those skilled in the art.

[0055] Example 1

[0056] A method for preparing a mesoporous copper-based catalyst for non-thermal plasma driven carbon dioxide hydrogenation to methanol.

[0057] The method comprises:

[0058] 1) 27.7 mL of 25 wt% hexadecyltrimethylammonium chloride aqueous solution, 27.7 mL of saturated ammonia water, and 320 mL of water were mixed evenly, 29.7 mL of tetraethoxysilane was added dropwise, and the mixture was stirred continuously at room temperature and hydrolyzed for 4 h to obtain a milky white mixed liquid, which was filtered, and the filter cake was washed alternately with water and ethanol and dried, and the solid was transferred to a muffle furnace and kept at 550° C. for 6 h to obtain a carrier;

[0059] 2) Take 0.15g of copper nitrate, 0.05g of lanthanum nitrate and 20mL of ethanol and mix them evenly, add 1g of the carrier for impregnation, stir at room temperature for 24h, and then stir at 35°C for volatilization until the solution is evaporated to dryness, dry the product, transfer the solid to a muffle furnace, keep the temperature at 470°C for 3h, grind and sieve for hydrogen reduction, mix hydrogen and argon in a ratio of 3:7 to obtain a mixed gas, introduce the mixed gas at a rate of 40mL / min, adjust the temperature to 400°C, and keep the temperature for 1h to obtain a mesoporous copper-based catalyst.

[0060] The hydrogenation catalytic performance of the mesoporous copper-based catalyst prepared in this example was tested using the following method.

[0061] The mesoporous copper-based catalyst of this example was subjected to non-thermal plasma-assisted catalytic carbon dioxide hydrogenation to methanol reaction in a dielectric barrier discharge non-thermal plasma reactor. The plasma was turned on and adjusted to 12.0 kV, 22.5 kHz, 70% H2 / Ar (70 mL / min) to reduce the catalyst in situ for 15 min, and then the raw gas (40 mL / min) with a molar ratio of H2:CO2=3:1 was introduced, and the plasma was adjusted to 13.0 kV, 22.5 kHz, the reaction pressure was atmospheric pressure, the reaction temperature was room temperature, and the mass space velocity was 16000 mL (STP) / g cat ·h.

[0062] 1. Carbon dioxide conversion rate

[0063] The carbon dioxide conversion rate is calculated according to the formula:

[0064]

[0065] 2. Methanol yield

[0066] The methanol space-time yield is calculated according to the formula:

[0067]

[0068] Wherein, m is the mass of methanol recovered, g, and m1 represents the maximum mass of methanol that can be converted into carbon dioxide, g;

[0069] 3. Methanol selectivity

[0070] Methanol selectivity was calculated according to the formula:

[0071]

[0072] Where m1 represents the methanol space-time yield, g·g cat ·h -1; t represents the reaction time; h, m2 represents the mass of the catalyst, g; m represents the mass of carbon dioxide consumed in the reaction, g;

[0073] 4. High temperature stability

[0074] 5 mg of the copper-based catalyst prepared in this example was weighed and placed in a crucible for drying. At 270°C, a mixture of nitrogen and protective gas was introduced at a flow rate of 55 mL / min (nitrogen and protective gas were uniformly mixed in a volume ratio of 3:7). The high-temperature stability of the catalyst was tested using a synchronous thermal analyzer. If the degree of degradation of each performance was less than 3%, it was marked as "√", otherwise it was marked as "×".

[0075] The results are as follows.

[0076] Carbon dioxide conversion rate (%) <![CDATA[Methanol yield (g·g cat / h)]]> Methanol selectivity (%) High temperature stability 15.3 0.25 19.0 √

[0077] According to the results in the table, the catalyst prepared by the present invention has high catalytic activity and high stability, and can efficiently convert carbon dioxide. Moreover, the catalyst can promote the adsorption and dissociation of carbon dioxide, and select the reaction path to proceed in the direction of methanol production, while inhibiting the production of CO through reverse water gas, thereby improving methanol selectivity.

[0078] Example 2

[0079] A method for preparing a mesoporous copper-based catalyst for non-thermal plasma driven carbon dioxide hydrogenation to methanol.

[0080] The method comprises:

[0081] 1) 27.7 mL of 25 wt% hexadecyltrimethylammonium chloride aqueous solution, 27.7 mL of saturated ammonia water, and 320 mL of water were mixed evenly, 29.7 mL of tetraethoxysilane was added dropwise, and the mixture was stirred continuously at room temperature and hydrolyzed for 4 h to obtain a milky white mixed liquid, which was filtered, and the filter cake was washed alternately with water and ethanol and dried, and the solid was transferred to a muffle furnace and kept at 550° C. for 6 h to obtain a carrier;

[0082] 2) Take 0.15g of copper nitrate, 0.24g of lanthanum nitrate and 20mL of ethanol and mix them evenly, add 1g of the carrier for impregnation, stir at room temperature for 24h, and then stir at 35°C for volatilization until the solution is evaporated to dryness, dry the product, transfer the solid to a muffle furnace, keep the temperature at 470°C for 3h, grind and sieve for hydrogen reduction, mix hydrogen and argon in a ratio of 3:7 to obtain a mixed gas, introduce the mixed gas at a rate of 40mL / min, adjust the temperature to 400°C, and keep the temperature for 1h to obtain a mesoporous copper-based catalyst.

[0083] The hydrogenation catalytic performance of the mesoporous copper-based catalyst prepared in this example was tested in the same manner as in Example 1, and the results are as follows.

[0084] Carbon dioxide conversion rate (%) <![CDATA[Methanol yield (g·g cat / h)]]> Methanol selectivity (%) High temperature stability 16.8 0.26 27.7 √

[0085] Part of the multivalent lanthanum oxide migrates to the catalyst surface, and the Cu + It is the active center for synthesizing methanol. In this example, the content of lanthanum trioxide is low, from which it can be seen that the CO selectivity of the catalyst in this example will be relatively low. With the increase of lanthanum nitrate dosage, the carbon dioxide conversion rate increases, and the methanol selectivity and yield increase.

[0086] Example 3

[0087] A method for preparing a mesoporous copper-based catalyst for non-thermal plasma driven carbon dioxide hydrogenation to methanol.

[0088] The method comprises:

[0089] 1) 27.7 mL of 25 wt% hexadecyltrimethylammonium chloride aqueous solution, 27.7 mL of saturated ammonia water, and 320 mL of water were mixed evenly, 29.7 mL of tetraethoxysilane was added dropwise, and the mixture was stirred continuously at room temperature and hydrolyzed for 4 h to obtain a milky white mixed liquid, which was filtered, and the filter cake was washed alternately with water and ethanol and dried, and the solid was transferred to a muffle furnace and kept at 550° C. for 6 h to obtain a carrier;

[0090] 2) Take 0.15g of copper nitrate, 0.56g of lanthanum nitrate and 20mL of ethanol and mix them evenly, add 1g of the carrier for impregnation, stir at room temperature for 24h, and then stir at 35°C for volatilization until the solution is evaporated to dryness, dry the product, transfer the solid to a muffle furnace, keep the temperature at 470°C for 3h, grind and sieve for hydrogen reduction, mix hydrogen and argon in a ratio of 3:7 to obtain a mixed gas, introduce the mixed gas at a rate of 40mL / min, adjust the temperature to 400°C, and keep the temperature for 1h to obtain a mesoporous copper-based catalyst.

[0091] The hydrogenation catalytic performance of the mesoporous copper-based catalyst prepared in this example was tested in the same manner as in Example 1, and the results are as follows.

[0092] Carbon dioxide conversion rate (%) <![CDATA[Methanol yield (g·g cat / h)]]> Methanol selectivity (%) High temperature stability 18.8 0.29 41.6 √

[0093] Based on lanthanum oxide as a promoter, the catalyst in this example has the characteristics of highly dispersed copper active sites, ordered mesoporous channels and high specific surface area, and exhibits high reactivity under non-thermal plasma conditions, and can be used to enhance the process of non-thermal plasma driven carbon dioxide hydrogenation to methanol, and improve the carbon dioxide conversion rate and methanol selectivity. According to the results in the table, in this example, with the assistance of non-thermal plasma, the catalyst has high catalytic activity, high carbon dioxide conversion rate, high methanol selectivity, and good catalyst stability.

[0094] Example 4

[0095] A method for preparing a mesoporous copper-based catalyst for non-thermal plasma driven carbon dioxide hydrogenation to methanol.

[0096] The method comprises:

[0097] 1) 27.7 mL of 25 wt% hexadecyltrimethylammonium chloride aqueous solution, 27.7 mL of saturated ammonia water, and 320 mL of water were mixed evenly, 29.7 mL of tetraethoxysilane was added dropwise, and the mixture was stirred continuously at room temperature and hydrolyzed for 4 h to obtain a milky white mixed liquid, which was filtered, and the filter cake was washed alternately with water and ethanol and dried, and the solid was transferred to a muffle furnace and kept at 550° C. for 6 h to obtain a carrier;

[0098] 2) Take 0.15g of copper nitrate, 0.90g of lanthanum nitrate and 20mL of ethanol and mix them evenly, add 1g of the carrier for impregnation, stir at room temperature for 24h, and then stir at 35°C for volatilization until the solution is evaporated to dryness, dry the product, transfer the solid to a muffle furnace, keep the temperature at 470°C for 3h, grind and sieve for hydrogen reduction, mix hydrogen and argon in a ratio of 3:7 to obtain a mixed gas, introduce the mixed gas at a rate of 40mL / min, adjust the temperature to 400°C, and keep the temperature for 1h to obtain a mesoporous copper-based catalyst.

[0099] The hydrogenation catalytic performance of the mesoporous copper-based catalyst prepared in this example was tested in the same manner as in Example 1, and the results are as follows.

[0100] Carbon dioxide conversion rate (%) <![CDATA[Methanol yield (g·g cat / h)]]> Methanol selectivity (%) High temperature stability 18.1 0.29 40.3 √

[0101] The present invention effectively synthesizes a mesoporous copper-based catalyst for catalyzing the hydrogenation of carbon dioxide to methanol under non-thermal plasma driving by adding lanthanum oxide as a promoter and adjusting the mass ratio of active metal copper and promoter lanthanum oxide in the catalyst. It is also analyzed that the catalyst can exhibit a relatively good catalytic effect under the non-thermal plasma driving with appropriate relative addition amounts of copper salt and lanthanum salt.

[0102] In summary, the catalyst prepared by the present invention has an extremely high specific surface area, stable and orderly mesoporous channels and the synergistic effect of copper and lanthanum on the carrier surface. Driven by non-thermal plasma, in a normal temperature and pressure environment, it can promote the reaction, efficiently activate carbon dioxide, and promote the reaction to the path of methanol synthesis, realizing the hydrogenation of carbon dioxide to methanol at low temperature and normal pressure.

[0103] Comparative Example 1

[0104] A method for preparing a mesoporous copper-based catalyst for non-thermal plasma driven carbon dioxide hydrogenation to methanol.

[0105] The method comprises:

[0106] 1) 27.7 mL of 25 wt% hexadecyltrimethylammonium chloride aqueous solution, 27.7 mL of saturated ammonia water, and 320 mL of water were mixed evenly, 29.7 mL of tetraethoxysilane was added dropwise, and the mixture was stirred continuously at room temperature and hydrolyzed for 4 h to obtain a milky white mixed liquid, which was filtered, and the filter cake was washed alternately with water and ethanol and dried, and the solid was transferred to a muffle furnace and kept at 550° C. for 6 h to obtain a carrier;

[0107] 2) Take 0.15g of copper nitrate and 20mL of ethanol and mix them evenly, add 1g of the carrier for impregnation, stir at room temperature for 24h, and then stir at 35°C for volatilization until the solution is evaporated to dryness, dry the product, transfer the solid to a muffle furnace, keep the temperature at 470°C for 3h, grind and sieve for hydrogen reduction, mix hydrogen and argon in a ratio of 3:7 to obtain a mixed gas, introduce the mixed gas at a rate of 40mL / min, adjust the temperature to 400°C, and keep the temperature for 1h to obtain a mesoporous copper-based catalyst.

[0108] The hydrogenation catalytic performance of the mesoporous copper-based catalyst prepared in this example was tested in the same manner as in Example 1, and the results are as follows.

[0109] Carbon dioxide conversion rate (%) <![CDATA[Methanol yield (g·g cat / h)]]> Methanol selectivity (%) High temperature stability 14.1 0.24 9.4 ×

[0110] In the technical solution of the present invention, the dispersion of copper species is increased, which is conducive to the activation of hydrogen in Cu 0 The activated carbon dioxide reacts on the lanthanum oxide site. 0 Hydrogen adsorption and dissociation, hydrogen atom overflow and hydrogenation of intermediates HCOO, H2COO, H2COOH, H2CO, the active C=O bond is first hydrogenated to form methanol, and the stable C=O bond is easily dehydrogenated to form CO. Under the drive of non-thermal plasma, an appropriate amount of lanthanum oxide can promote the conversion of carbon dioxide. In addition, the catalyst in this example cannot maintain its original crystal structure during the calcination process, and the interaction between the copper species and the carrier becomes worse, resulting in a decrease in the carbon dioxide conversion rate.

[0111] Combined with the results in the table, it is found that compared with a single copper-based catalyst, the lanthanum oxide-supported copper-based catalyst of the present invention has a stronger catalytic activity. Carbon dioxide is adsorbed on the multivalent lanthanum oxide and activated to form an intermediate oxygen. At the same time, hydrogen is absorbed on the Cu 0 The synergistic effect of the two is beneficial to improving the methanol yield.

[0112] Comparative Example 2

[0113] A method for preparing a mesoporous copper-based catalyst for non-thermal plasma driven carbon dioxide hydrogenation to methanol.

[0114] The method comprises:

[0115] 1) 27.7 mL of 25 wt% hexadecyltrimethylammonium chloride aqueous solution, 27.7 mL of saturated ammonia water, and 320 mL of water were mixed evenly, 29.7 mL of tetraethoxysilane was added dropwise, and the mixture was stirred continuously at room temperature and hydrolyzed for 4 h to obtain a milky white mixed liquid, which was filtered, and the filter cake was washed alternately with water and ethanol and dried, and the solid was transferred to a muffle furnace and kept at 550° C. for 6 h to obtain a carrier;

[0116] 2) Take 0.56g of lanthanum nitrate and 20mL of ethanol and mix them evenly, add 1g of the carrier for impregnation, stir at room temperature for 24h, and then stir at 35°C for volatilization until the solution is evaporated to dryness, dry the product, transfer the solid to a muffle furnace, keep the temperature at 470°C for 3h, grind and sieve for hydrogen reduction, mix hydrogen and argon in a ratio of 3:7 to obtain a mixed gas, introduce the mixed gas at a rate of 40mL / min, adjust the temperature to 400°C, and keep the temperature for 1h to obtain a mesoporous catalyst.

[0117] The hydrogenation catalytic performance of the mesoporous copper-based catalyst prepared in this example was tested in the same manner as in Example 1, and the results are as follows.

[0118] Carbon dioxide conversion rate (%) <![CDATA[Methanol yield (g·g cat / h)]]> Methanol selectivity (%) High temperature stability 14.9 0.25 21.9 ×

[0119] In this case, lanthanum oxide is highly dispersed on the support surface and has a high density of active sites, but the driving force generated by the activation of carbon dioxide through lanthanum oxide sites alone cannot achieve efficient conversion of carbon dioxide. Smaller particles are formed on the catalyst surface and the selectivity for methanol is low.

[0120] Comparative Example 3

[0121] A method for preparing a mesoporous copper-based catalyst for non-thermal plasma driven carbon dioxide hydrogenation to methanol.

[0122] The method comprises:

[0123] 1) 27.7 mL of saturated hexadecyltrimethylammonium chloride aqueous solution, 27.7 mL of saturated ammonia water, and 320 mL of water were mixed evenly, 29.7 mL of tetraethoxysilane was added dropwise, and the mixture was stirred continuously at room temperature and hydrolyzed for 4 h to obtain a milky white mixed liquid, which was filtered, and the filter cake was alternately rinsed with water and ethanol and dried, and the solid was transferred to a muffle furnace and kept at 550° C. for 6 h to obtain a carrier;

[0124] 2) Take 0.15g of copper nitrate, 0.56g of lanthanum nitrate and 20mL of ethanol and mix them evenly, add 1g of the carrier for impregnation, stir at room temperature for 24h, and then stir at 35°C for volatilization until the solution is evaporated to dryness, dry the product, transfer the solid to a muffle furnace, keep the temperature at 470°C for 3h, grind and sieve for hydrogen reduction, mix hydrogen and argon in a ratio of 3:7 to obtain a mixed gas, introduce the mixed gas at a rate of 40mL / min, adjust the temperature to 400°C, and keep the temperature for 1h to obtain a mesoporous copper-based catalyst.

[0125] The hydrogenation catalytic performance of the mesoporous copper-based catalyst prepared in this example was tested in the same manner as in Example 1, and the results are as follows.

[0126] Carbon dioxide conversion rate (%) <![CDATA[Methanol yield (g·g cat / h)]]> Methanol selectivity (%) High temperature stability 13.5 0.24 9.6 √

[0127] In the soft template method, the concentration of the template solution and the arrangement of the hexadecyltrimethylammonium chloride molecules will directly affect the morphology of the pores. In this case, the concentration of the template solution was increased, and the pore volume of the prepared catalyst increased significantly, and the molecules aggregated to form a larger space, which was conducive to the loading of active species. However, in actual applications, the pore walls of the catalyst were prone to cracking, resulting in a decrease in its catalytic activity.

[0128] Comparative Example 4

[0129] A method for preparing a mesoporous copper-based catalyst for non-thermal plasma driven carbon dioxide hydrogenation to methanol.

[0130] The method comprises:

[0131] Take 27.7 mL of 25 wt% zinc-phenyl polyoxyethylene ether, 27.7 mL of saturated ammonia water, and 320 mL of water, mix them evenly, add 29.7 mL of tetraethoxysilane dropwise, continue stirring at room temperature, hydrolyze for 4 hours to obtain a milky white mixed liquid, filter it, rinse the filter cake alternately with water and ethanol and dry it, transfer the solid to a muffle furnace, and keep the temperature at 550°C for 6 hours to obtain the carrier.

[0132] In this case, the zinc-phenyl polyoxyethylene ether molecule can also make the crystal grow along the spatial structure formed by the molecule, but unlike the pore structure formed by the hexadecyl trimethyl ammonium chloride molecule, the pore structure of the carrier prepared in this case is relatively irregular. Most importantly, the molecular structure of the carrier becomes less orderly, and the skeleton collapses during the high-temperature removal of the template, and a mesoporous carrier material with an orderly structure cannot be formed.

[0133] Comparative Example 5

[0134] A method for preparing a mesoporous copper-based catalyst for non-thermal plasma driven carbon dioxide hydrogenation to methanol.

[0135] The method comprises:

[0136] Take 0.15g of copper nitrate, 0.56g of lanthanum nitrate, and 20mL of ethanol and mix them evenly, add 1g of aluminum oxide for impregnation, stir at room temperature for 24h, and then stir at 35°C for volatilization until the solution is evaporated to dryness. Dry the product, transfer the solid to a muffle furnace, keep the temperature at 470°C for 3h, grind and sieve for hydrogen reduction, mix hydrogen and argon in a ratio of 3:7 to obtain a mixed gas, introduce the mixed gas at a rate of 40mL / min, adjust the temperature to 400°C, and keep the temperature for 1h to obtain a mesoporous copper-based catalyst.

[0137] The hydrogenation catalytic performance of the mesoporous copper-based catalyst prepared in this example was tested in the same manner as in Example 1, and the results are as follows.

[0138] Carbon dioxide conversion rate (%) <![CDATA[Methanol yield (g·g cat / h)]]> Methanol selectivity (%) High temperature stability 11.4 0.20 9.1 ×

[0139] In this case, the ordered mesoporous silica carrier was replaced with alumina for research. Alumina also has a supporting role, which can disperse the active components of the catalyst and improve the carbon dioxide conversion rate. However, due to the hydrophilicity of alumina, the methanol production rate decreases, and the catalytic activity of the catalyst decreases under the influence of water molecules, resulting in a decrease in the carbon dioxide conversion rate, which leads to a low methanol yield.

[0140] Comparative Example 6

[0141] A method for preparing a mesoporous copper-based catalyst for non-thermal plasma driven carbon dioxide hydrogenation to methanol.

[0142] The method comprises:

[0143] 1) 27.7 mL of 25 wt% hexadecyltrimethylammonium chloride aqueous solution, 27.7 mL of saturated ammonia water, and 320 mL of water were mixed evenly, 29.7 mL of tetraethoxysilane was added dropwise, and the mixture was stirred continuously at room temperature and hydrolyzed for 4 h to obtain a milky white mixed liquid, which was filtered, and the filter cake was washed alternately with water and ethanol and dried, and the solid was transferred to a muffle furnace and kept at 550° C. for 6 h to obtain a carrier;

[0144] 2) Take 0.15g of copper nitrate, 0.56g of lanthanum nitrate and 20mL of ethanol and mix them evenly, add 1g of the carrier for impregnation, stir at room temperature for 24h, and then stir at 35°C for volatilization until the solution is evaporated to dryness, dry the product, transfer the solid to a muffle furnace, keep the temperature at 550°C for 3h, grind and sieve for hydrogen reduction, mix hydrogen and argon in a ratio of 3:7 to obtain a mixed gas, introduce the mixed gas at a rate of 40mL / min, adjust the temperature to 400°C, and keep the temperature for 1h to obtain a mesoporous copper-based catalyst.

[0145] The hydrogenation catalytic performance of the mesoporous copper-based catalyst prepared in this example was tested in the same manner as in Example 1, and the results are as follows.

[0146] Carbon dioxide conversion rate (%) <![CDATA[Methanol yield (g·g cat / h)]]> Methanol selectivity (%) High temperature stability 12.7 0.22 10.5 ×

[0147] High calcination temperature will not only cause particle agglomeration, resulting in decreased porosity, and easy collapse of the pores, the decrease in the specific surface area and pore volume of the catalyst active components, but also cause the order of the carbonized structure to be slightly damaged, the C-Si skeleton to deform, and the carbon dioxide conversion rate to be significantly reduced. At the same time, the copper species particle size increases, resulting in a decrease in methanol selectivity. It can be seen that the calcination temperature has an important influence on the preparation of the catalyst of the present invention. In order to ensure the performance of the catalyst, its calcination conditions should be controlled.

Claims

1. A method for preparing a mesoporous copper-based catalyst, characterized in that: The method comprises: 1) taking a template solution, an alkali solution and a dispersant and mixing them evenly, adding an organosilicon compound dropwise to hydrolyze to obtain a milky white mixed solution, filtering the mixed solution, washing the filter cake and drying it, and calcining the mixture to obtain a carrier; 2) Evenly mix copper salt, lanthanum salt and solvent, add the mixture into a carrier for impregnation, dry, calcine, grind and screen the product and reduce it with hydrogen to obtain a mesoporous copper-based catalyst.

2. The method for preparing a mesoporous copper-based catalyst according to claim 1, characterized in that: Step 1) the template solution is a hexadecyltrimethylammonium chloride aqueous solution with a concentration of 20-25 wt.%; Step 1) The alkali solution is saturated ammonia water, and its dosage is 0.97-6.49 mL / mL template solution; Step 1) The dispersant is water, and its dosage is 10-15 mL / mL template solution; In step 1), the organosilicon compound is tetraethoxysilane, and its usage is 0.92-2.77 mL / mL template solution.

3. The method for preparing a mesoporous copper-based catalyst according to claim 1 or 2, characterized in that: The hydrolysis in step 1) is carried out under continuous stirring at room temperature for 4 to 5 hours; Step 1) The calcination is carried out at 500-600° C. for 5-7 hours.

4. The method for preparing a mesoporous copper-based catalyst according to claim 1, characterized in that: Step 2) the copper salt is copper nitrate and / or copper acetate and / or copper chloride and / or copper oxalate and / or copper sulfate and / or copper acetylacetonate; Step 2) the lanthanum salt is lanthanum nitrate and / or lanthanum acetate and / or lanthanum oxalate and / or lanthanum acetylacetonate and / or lanthanum chloride and / or lanthanum sulfate; Step 2) The copper salt and the lanthanum salt are prepared in a mass ratio of 1: (0.3-6.0).

5. The method for preparing a mesoporous copper-based catalyst according to claim 1 or 4, characterized in that: Step 2) the solvent is ethanol, and the amount used is 115-155 mL / g copper salt; Step 2) The amount of the carrier used is 5.9-7.7 g / g copper salt.

6. The method for preparing a mesoporous copper-based catalyst according to claim 1, characterized in that: Step 2) The impregnation process is: Stir at room temperature for 22 to 26 hours, then stir at 30 to 40°C to evaporate until the solution is evaporated to dryness; Step 2) The calcination is carried out at 400-500° C. for 2-4 hours.

7. The method for preparing a mesoporous copper-based catalyst according to claim 1, characterized in that: Step 2) The hydrogen reduction process is: Hydrogen and argon are mixed in a ratio of (2-4):7 to obtain a mixed gas, and the mixed gas is introduced at a rate of 40-45 mL / min. The temperature is adjusted to 300-500° C. and maintained at a constant temperature for 1-2 hours.

8. A mesoporous copper-based catalyst prepared by the method of any one of claims 1 to 7.